KONSEP PENDIDIKAN AKHLAK DAN PENGUATAN KARAKTER INDIVIDU DI ERA MILENIAL - Hadi Muhaini (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2019)
Abstraksi: In this millennial era, there are a lot of challenges that educators and learners have to face. The technological sophistication and flow of information that comes in and out of the nation's young generation is very influential in the students ' personality. It is this problem that demands the students to always cling to the values of religious teachings that he lived. Sexual and ethical education is indispensable to students in order to face this digital millennial era. Actually, the technological sophistication of this era can have positive and negative impact on how we are addressing and utilizing it. When used on positive matters, this technology is beneficial. Conversely when used on negative things it will harm itself. In addition to sexual education, character strengthening is also indispensable for learners. Character reinforcement can be gained and learned from teachers through ethical education both in the school and through family, places of worship and also through good community life.Key Words: Religious Teachings, Education, Character